Compensation in a fluvial system: the study case of the Parismina River, Costa Rica - Chaves-Quirós, Anny (2022)
Introduction: The construction of the Reventazón Hydroelectric Project (PH) was the sixth development in the main channel of the Reventazón river in the Caribbean of Costa Rica. Objective: This project identified residual and cumulative impacts on the main river system, and here we describe how those impacts were compensated. Methods: Based on baseline studies, the habitat lost in the Reventazón River due to the hydroelectric project was quantified, particularly in the area currently occupied by its reservoir and the section up to the PH Angostura dam. In addition, the environmental gain that would result from protecting the Parismina-Dos Novillos rivers, which are part of the same drainage system, was evaluated. The potential compensation was fulfilled by declaring the Parismina-Dos Novillos as a river system free of barriers, that is, free of future hydroelectric dams, and by promoting a series of management programs that were implemented on the banks of those rivers. To demonstrate the non-loss of biodiversity, an expression was used that compares the expected improvement in the quality of the aquatic habitat in the Parismina-Dos Novillos river with the loss of aquatic habitat in the Reventazón river. Results: By executive decree, the program for the conservation and sustainable use of the Parismina-Dos Novillos fluvial system was declared of public interest as a river without barriers and called the “Parismina and Dos Novillos Fluvial Compensation Program.” In addition, the Bobo-Fish Biological Corridor was established, including this river system and protecting its biodiversity. Conclusions: The Parismina Fluvial Compensation Program provides an alternative to compensate for residual impacts on aquatic systems. It could serve as a reference framework to achieve environmental gains in these riverine systems.